Answer:
a(4,3). b( 2,3). c(4,-1). d(-2,-1/2). e(5/2, 0).
Explanation:
Hello , I can help you with that
the mid point is given by
Let
Point 1
![(x_(1),y_(1))](https://img.qammunity.org/2021/formulas/mathematics/college/thi732wso94q73aqhypel0qxm0vldobtmf.png)
Point 2
![(x_(2),y_(2))](https://img.qammunity.org/2021/formulas/mathematics/college/63yqidxkuznij2ybdvegcbzycem4337jvv.png)
the midpoint is(m)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )](https://img.qammunity.org/2021/formulas/mathematics/high-school/xp2ayork29ic4p3lm4zbuvaf73crvmymst.png)
all you have to do is to put those values into the equation
Step 1
P1(3,4) and P2(5,2)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )\\m=((3+5)/(2),(4+2)/(2) )\\m=((8)/(2),(6)/(2) )\\m=(4,3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lgg35z33rpwu56hgczdppqcbcrgx2iacyp.png)
Step 2
P1(0,6) and P2(4,0)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )\\m=((0+4)/(2),(6+0)/(2) )\\m=((4)/(2),(6)/(2) )\\m=(2,3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7kv5fti0menwuxff2vt9yqayoq518xvszi.png)
Step 3
P1(4,2) and P2(4,-4)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )\\m=((4+4)/(2),(2-4)/(2) )\\m=((8)/(2),(-2)/(2) )\\m=(4,-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/yjbjdskqwpacjvg7zgv81gamjoeynznnm7.png)
Step 4
P1(-1,-5) and P2(-3,4)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )\\m=((-1-3)/(2),(-5+4)/(2) )\\m=((-4)/(2),(-1)/(2) )\\m=(-2,(-1)/(2) )](https://img.qammunity.org/2021/formulas/mathematics/high-school/lgx6e8s8k7f64wr8hucce6dtzi24v9a9u1.png)
Step 5
P1(-3,2) and P2(8,-2)
![m=((x_(1)+x_(2))/(2),(y_(1)+y_(2))/(2) )\\m=((-3+8)/(2),(2-2)/(2) )\\m=((5)/(2),(0)/(2) )\\m=((5)/(2) ,0)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sa832xhlgoao1mww7vjsgl3fem6xo06wm9.png)
I really hope it helps you, have a nice day